2020
DOI: 10.1186/s12889-020-09316-x
|View full text |Cite
|
Sign up to set email alerts
|

Intention to use vasectomy and associated factors among married men in Addis Ababa, Ethiopia

Abstract: Background Vasectomy is one of the highly effective and non-reversible types of long-term family planning methods for men. Ethiopia has a limited number of studies on the use of vasectomy, and they are focused on men rather than married men. The current study was aimed to identify the intention to use vasectomy as a method of contraception among married men in the study setting. Methods A community-based cross-sectional study was conducted from February 1 – April 30, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 14 publications
4
6
0
Order By: Relevance
“…In this study, 48.4% (95% CI 44.4–52.4%) of married men who had ever heard about vasectomy had a positive attitude towards vasectomy, which was higher than the studies conducted in Nigeria, Addis Ababa, and Gonder (18%, 23.2%, and 15.9%, respectively). 7 , 11 , 18 In Iran, only 21.2% had good attitudes toward vasectomy, and about 44% had weak attitudes toward vasectomy. 16 The reason may be due to the study year and area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, 48.4% (95% CI 44.4–52.4%) of married men who had ever heard about vasectomy had a positive attitude towards vasectomy, which was higher than the studies conducted in Nigeria, Addis Ababa, and Gonder (18%, 23.2%, and 15.9%, respectively). 7 , 11 , 18 In Iran, only 21.2% had good attitudes toward vasectomy, and about 44% had weak attitudes toward vasectomy. 16 The reason may be due to the study year and area.…”
Section: Discussionmentioning
confidence: 99%
“…Among those who had ever heard about vasectomy, 60.6% (95% CI 56.6–64.6%) of the married men had good knowledge about vasectomy; this finding is higher than studies conducted in Edo state, Nigeria, Gonder, Dangila, Western Nepal, and Debre Tabor. 9–11 , 18 This may be due to differences in study participants’ socio-demographic characteristics, year of study, and sample size.…”
Section: Discussionmentioning
confidence: 99%
“… 33 Studies in Ethiopia found knowledge of vasectomy to be associated with an individual’s level of education, 34 , 35 positive attitude toward vasectomy, and intention to use vasectomy. 36 , 37 …”
Section: Discussionmentioning
confidence: 99%
“…33 Studies in Ethiopia found knowledge of vasectomy to be associated with an individual's level of education, 34,35 positive attitude toward vasectomy, and intention to use vasectomy. 36,37 Furthermore, in surveys of contraceptive use, "knowledge" of vasectomy relates to whether respondents have heard of or are aware of the method but not necessarily to whether they have accurate or correct understanding of it. 38 Vasectomy is the method most plagued by widespread, deep-seated, and persistent myths and misunderstandings about it and biases against it.…”
Section: Awareness and Accurate Understandingmentioning
confidence: 99%
“…Many other studies on vasectomy in West Africa reviewed report that fear, and religious and cultural beliefs, which are also framed as a lack of knowledge, contribute to the poor uptake of vasectomy in the region. [40][41][42][43] . These studies recommend increased publicity and public awareness campaigns on vasectomy.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%